Improving the Fine Motor Skills with Embroidery among Children with an Intellectual Disability - Syiddatul Budury; Khamida Khamida; Siti Nurjanah; Triana Jamaliah Jalaluddin (Jurnal Ners, 2020)
Introduction: Children with intelletual disability experience delays infine motor skills compared to normal children, if the child's fine motor skills are not trained and developed, it will affect to the child's growth and development. One of occupational therapies to improve their finemotor skills is through embroidery. The purpose of this study was to analyze the effect of embroidery to the fine motor development of children with moderate mental retardation at the special school, Bangkalan Indonesia.Methods: The design was pre experimental research with one pre test-post test design group, population of all children with moderate mental retardationas many as 13 children. The research instrument use dwasobservation sheet.Results: Data analysisby Wilcoxon Signed Ranks Test.The embroidery therapy using cross stitch technique. It was held every Monday and Thursday for eight week, took an hour each sessionConclusion: The results of the study showed that most children after had embroidery had enough finemotor skills (84.6%) and the statistical test value was obtained p<α (0.002<0.05). The students improved their fine motor ability such as how they coloring, scissoring, grasping, and holding up a paper. The conclusion of this study is that there was an effect of embroidery therapy on fine motor skills in children with intellectual disability.